2013
DOI: 10.1371/journal.pone.0074087
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between γ-Aminobutyric Acid A Receptor Genes: New Evidence in Migraine Susceptibility

Abstract: Migraine is a common neurological episodic disorder with a female-to-male prevalence 3- to 4-fold higher, suggesting a possible X-linked genetic component. Our aims were to assess the role of common variants of gamma-aminobutyric acid A receptor (GABAAR) genes, located in the X-chromosome, in migraine susceptibility and the possible interaction between them. An association study with 188 unrelated cases and 286 migraine-free controls age- and ethnic matched was performed. Twenty-three tagging SNPs were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
0
19
1
Order By: Relevance
“…This SNP has also been analyzed as a putative risk factor for essential tremor, with negative findings (Garcia-Martin et al, 2011a ). A putative association of heterozygosity (T/A genotype) with increased risk of developing migraine has been described (Quintas et al, 2013 ), although these findings could not be replicated by our group (García-Martín et al, 2018 ). GABRR1 SNPs rs1186902 and rs12200969 were analyzed as putative risk factors related to ethanol dependence, but no association was identified (Xuei et al, 2010 ).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…This SNP has also been analyzed as a putative risk factor for essential tremor, with negative findings (Garcia-Martin et al, 2011a ). A putative association of heterozygosity (T/A genotype) with increased risk of developing migraine has been described (Quintas et al, 2013 ), although these findings could not be replicated by our group (García-Martín et al, 2018 ). GABRR1 SNPs rs1186902 and rs12200969 were analyzed as putative risk factors related to ethanol dependence, but no association was identified (Xuei et al, 2010 ).…”
Section: Discussioncontrasting
confidence: 64%
“…Regarding the putative clinical associations for these polymorphisms, the GABRG2 SNP designated as rs211035 was previously investigated in relation to epilepsy with negative results (Dixit et al, 2016 ). It has been proposed that the GABR E SNP designated as rs1139916 affects the binding of extracellular ligands, and it has been associated with migraine risk in women, with carriers of variant alleles being at decreased risk (Quintas et al, 2013 ). Our own findings confirm this observation (García-Martín et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fern andez et al 47 showed lack of association between common SNPs in these genes and the risk for migraine in a case-control association study, which included GABRE3 rs2050843 (192 cases/142 controls), GABRE5 rs2256882 (177 cases/135 controls), a GABRE9 novel SNP (158 cases/100 controls), and GABRQ rs8810652 (202 cases/155 controls), and a trend toward a nonsignificant increased frequency of the GABRQ rs8810652TT genotype in patients with MWoA compared with those with MWA. In contrast, Quintas et al, 48 in other case-control association study involving 153 cases and 217 controls, described increased risk for migraine in carriers of the GABRQ rs3810651AT genotype, and in males carrying the allele T of the GABRE rs5925077 variant or the allele C of the GABRA3 rs2201169 variant; and decreased risk in carriers of the GABRA3 rs3902802CT and GABRA3 rs2131190GA genotype, while they found no association with other tagging SNPs in the GABRA3, GABRQ, and GABRE genes. C. Chen et al 49 described lack of association between the GABRG2 rs211037 variant and the risk for migraine in a case-control association study involving 245 patients and 247 controls.…”
Section: Gaba and Cortical Spreading Depression (Csd)mentioning
confidence: 90%
“…Migraine is a neurological disorder manifested by attacks of idiopathic and recurrent headaches. Genes on chromosomes 1, 2, 8 and X have linked to migraine [1] , [2] , [3] . The classification established by the International Headache Society (IHS) in 2004 identified two types: migraine without aura (MSA), the most common form, which is isolated headache, and migraine with aura (MA) where the headache is preceded or accompanied by a focal neurological disorder, transient and progressive (visual disturbances, paresthesia, speech disorder, movement disorders) [4] , [5] .…”
Section: Introductionmentioning
confidence: 99%